Instrumental Activities of Daily Living (iADL) Limitations in Europe: An Assessment of SHARE Data - Portela, Diana (Int J Environ Res Public Health, 2020)
This study aims to evaluate the instrumental activities of daily living (iADLs) limitations in Europe and its association with socio-demographic characteristics, economic parameters and physical and mental health status. We used data from the wave 6 of SHARE database. Individuals were classified as having either none or one or more limitations on iADLs. Participants aged 65 or more years who answered all questions for the variables included in this work were selected. A total of 54.8% of participants were female and had a mean age of 74.37 (SD = 7.08) years. A global prevalence of 1 or more iADLs in Europe was shown to be 23.8% and more prevalent in women than in men (27.1% vs. 17.6%) and in people aged 85 years or more (51.5%). Older age, female gender, lower education, physical inactivity, frailty, having two or more chronic diseases, presence of depression, polypharmacy, poor self-perception of health and lower network satisfaction were found to be factors associated with the presence of 1 or more iADLs limitation. This study highlights the burden of iADLs limitations at the European level. These are based on a multidimensional biopsychosocial model and are associated with both health conditions and environmental factors. This intersection between the physical and social world underscores its potential as a health indicator and can, to some extent, explain some of the pronounced differences seen among European countries. Different inter-tasks can also stress different dimensions of health indicators in distinct and specific groups of individuals. Minimizing the impact of iADL limitations can improve the quality and sustainability of public health systems.